Cryptosporidium occultus sp. n. (Apicomplexa: Cryptosporidiidae) in rats - Kváč, Martin; Vlnatá, Gabriela; Ježková, Jana; Horčičková, Michaela; Konečný, Roman; Hlásková, Lenka; McEvoy, John; Sak, Bohumil (European journal of protistology, 2018)
Cryptosporidium parvum VF383 has been reported in humans, domesticated ruminants, and wild rats worldwide and described under several names including Cryptosporidium suis-like, based on its close phylogenetic relationship to C. suis. Unlike C. suis, however, it has never been detected in pigs. In the present work, C. parvum VF383 originating from wild brown rats was not infectious for piglets or calves but was infectious for laboratory brown rats, BALB/c mice, and Mongolian gerbils. The prepatent period was 4-5 days for all rodents. The patent period was longer for rats (>30 days) than other rodents (<20 days). None of the rodents developed clinical signs of infection. In all rodents, life cycle stages were detected in the colon by histology and electron microscopy. Oocysts were morphometrically similar to those of C. parvum and smaller than those of C. suis, measuring 5.20 × 4.94 μm. Phylogenetic analyses of 18S rRNA, actin, and HSP70 gene sequences revealed C. parvum VF383 to be genetically distinct from, C. suis, and other described species of Cryptosporidium. Morphological, genetic, and biological data support the establishment of C. parvum VF383 as a new species, and we propose the name Cryptosporidium occultus sp. n.
Keywords: kolon; druhová specificita; Molecular phylogeny; Actins; Transmission studies; proteiny tepelného šoku HSP70; HSP70 Heat-Shock Proteins; RNA, Ribosomal, 18S; kryptosporidióza; Morphometry; Cryptosporidiosis; Species Specificity; aktiny; krysa rodu Rattus; Animals; zvířata; Colon; Rats; Cryptosporidium; RNA ribozomální 18S; New species; Histology